Implementation Of Movement Detection And Tracking Objects From Video Frames Using Image Processing - G. Mallikharjuna Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The moment detection and tracking in a video surveillance system video is a challenging framework. This paper aimed to detect the motion from video frames of compressor JPEG format. The approaches for motion detection using the sum of absolute difference. Once after performing motion detection, tracking the objects is processed for behavioral analysis. A Kalman filter method is applied to predict the position of an object. The video from the stationary camera and static background trajectory movement, and the direction of an object are relatively synchronized. The foreground detection and Kalman filters are used for object detection and motion tracking, respectively.